Comparison between Intrathecal Dexmedetomidine & Bupivacaine Vs Bupivacaine Alone for Prevention of Shivering in C-Section - Abaid-Ur-Rehman, Zeeshan Khan, Amjad Nadeem, Muhammad Muazzam Butt, Mohsin Riaz Askri, Zulqarnain Butt (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Shivering is one of the very common side effects of spinal anesthesia. It can be extremely discomforting for parturient undergoing caesarean section. Aim: To compare intrathecal dexmedetomidine and bupivacaine with bupivacaine alone to see whether intrathecal dexmedetomidine can be helpful in preventing shivering in cases undergoing C-section Methodology: This was a prospective randomized controlled trial carried out at Department of Anaesthesiology, Sheikh Zayed Hospital, Rahim Yar Khan. In this study all pregnant females undergoing C section between the age of 18 to 40 years irrespective of their gravida and parity were included. The cases were divided into two equal groups B and D. Group B were offered injection Bupivacaine only and those in group D were offered Bupivacaine along with Dexmedetomidine. Final outcome was seen at 4 hours for shivering after giving spinal anesthesia. Results: In this study there were 120 cases, 60 in each group. The mean age in group B and D was 31.12±4.57 vs 30.67±5.03 years with p value 0.81 and mean BMI was23.19±4.11 vs 23.81±4.23 kg/m2 with P value 0.95 respectively. There were 80% cases in group B and 66.67% in group D belonging to rural population with p value 0.88. Shivering was observed in 24 (40%) cases in group B and 6(10%) in group D with p value 0.01. Conclusion: Combination of intrathecal Bupivacaine and Dexmedetomedine is significantly better than intra thecal Bupivacaine alone in prevention of shivering in patients undergoing C section.